Associations between prematurity, postpartum anxiety, neonatal intensive care unit admission, and stress - Worrall, Semra; Christiansen, Paul; Khalil, Asma; Silverio, Sergio A.; Fallon, Victoria (Frontiers in Psychiatry, 2024)
Abstract Introduction: It is well established that a premature birth increases the likelihood of developing anxiety during the postpartum period, and that the environment of the neonatal intensive care unit [NICU] might be a contributing factor. Mothers of earlier premature infants may experience these anxieties to a higher degree compared to mothers of later premature infants. The aim of this study was to explore the association between prematurity and postpartum-specific anxiety, and the relationship between postpartum-specific anxiety and stress in the neonatal intensive care unit. Materials and Methods: Mothers (N=237) of infants aged between birth and 12 months completed on online survey containing the Postpartum Specific Anxiety Scale – Research Short Form [PSAS-RSF] and the Parental Stressor Scale: Neonatal Intensive Care Unit [PSS:NICU]. Structural equation modelling was used to analyse the relationship between gestational age and postpartum-specific anxiety, with one-way ANOVAs used to analyse this relationship with respect to categories of gestational age. Hierarchical regression models analysed the relationship between postpartum-specific anxiety and stress in NICU. Results: For the PSAS-RSF, Practical Infant Care Anxieties (p=.001), Maternal Competence and Attachment Anxieties (p=.033), and Infant Safety and Welfare Anxieties (p=.020) were significantly associated with week of gestation. Practical Infant Care and Infant Safety and Welfare Anxieties were significantly higher for mothers of late premature infants, compared to mothers of term infants (p<.001; p=.019). There were no significant between-group differences with respect to Maternal Competence and Attachment Anxieties. After controlling for potential confounders, Infant Safety and Welfare Anxieties were significantly associated with increased stress in the NICU (p<.001) as measured by the PSS:NICU. Conclusions: Our findings highlight the need for interventions for mothers with premature infants which specifically target anxieties reflected in the PSAS-RSF, such as routine care and increasing maternal self-efficacy.